Emergence of Boron and Sulphur Deficiency in Soils of Chandauli, Mirzapur, Sant Ravidas Nagar and Varanasi Districts of Eastern Uttar Pradesh - Singh, Dileep Kumar, Omkar Kumar, S.N.Yadav; S.S. Verma, S.K. Singh, P. Dey, Surendra Singh, P. K. Sharma, Y.V. Singh, A.M. Latare, C.M (Journal of the Indian Society of Soil Science, 2015)
Two thousand three hundred thirty four surface soil samples were collected from Chandauli, Mirzapur, Sant Ravidas Nagar and Varanasi districts of eastern Uttar Pradesh during 2011-12 under GPS and GIS based soil fertility mapping project. Analysis of these soil samples revealed the occurrence of acidic soils (pH <5.5) in Chandauli and Mirzapur districts. A wide variation in pH (4.5-10.4) indicated acidic to alkali nature of the soils in this region. These soils have electrical conductivity (EC) less than 1 dS m-1 and organic carbon (OC) content ranged from 0.6 to 13.3 g kg-1. High OC content was noticed in some Vindhyan low land soils of Chandauli and Mirzapur district. Available sulphur (S) content ranged from 0.43 to 165 mg kg-1 with a mean value of 16.10, 9.63, 13.05 and 12.36 mg kg-1 in Chandauli, Mirzapur, Sant Ravidas Nagar and Varanasi districts, respectively. The corresponding deficiency of S in soils of these districts was 39, 63, 45 and 56 per cent. Nutrient index (NI) indicated S fertility level of low to medium. Soils were also found to be highly deficient in available boron (B), with mean contents of 0.55, 0.49, 0.66 and 0.62 mg kg-1 in Chandauli, Mirzapur, Sant Ravidas Nagar and Varanasi districts, respectively showing deficiency in 55, 61, 30 and 37 per cent soil samples. High magnitude of B deficiency was noticed in soils of Vikas Khand Nawgarh (94%) followed by Rajgarh (85%) and Marihan (80%), representing the area of low pH Vindhyan soils.